Pemanfaatan Maggot Sebagai Organisme Kecil Pengolah Sampah Organik - Kusumaningsih, Rila (LPPM Universitas Bumigora, 2024)
Each major city in Indonesia generally produces about 10 tonnes of waste per year. Efforts and strategies in effective waste management are to manage waste from its source. One of the sources of waste generation is households. The solution to the waste problem can be solved with bioconversion technology using insects. Black Soldier Fly (BSF) functions to decompose organic waste to produce economic value. The cultivation of maggots (Hermetia illuciens) in addition to breaking down organic waste can also be used as a source of animal feed. Black Soldier Fly (BSF) larvae are used as an alternative animal feed because they have a high source of protein. Biomass from waste products produced by maggot can still be used as a support in agricultural activities that can be used as organic fertiliser. Compost from maggot waste is part of the circular economy and zero waste measures. The implementation of this service aims to provide insight and knowledge and understanding of how to manage waste and recycle waste so as to produce a new product that is beneficial for plant survival and to socialise the use of maggot as a small organic waste processing organism is an important step in utilising waste into a useful result and the realisation of a healthy environment.